2021
DOI: 10.5705/ss.202018.0219
|View full text |Cite
|
Sign up to set email alerts
|

Copula-based Partial Correlation Screening: a Joint and Robust Approach

Abstract: Screening for ultrahigh dimensional features may encounter complicated issues such as outlying observations, heterogeneous or heavy-tailed distribution, multi-collinearity and confounding effects. Standard correlation-based marginal screening methods may be a weak solution to these issues. We contribute a novel robust joint screener to safeguard against outliers and distribution mis-specification for both the response variable and the covariates, and to account for external variables at the screening step. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In addition, (11) indicates that the proposed method is able to handle the nonpolynomial (NP) dimensionality with p=ofalse{exp(n12κ)false}$p = o\lbrace \exp (n^{1-2\kappa })\rbrace$, which is parallel with other feature screening methods, such as distance correlation (Li et al., 2012b) or the rank concordance–based estimating equation (Ma et al., 2017). On the other hand, different from other feature screening methods that may require additional assumptions to establish theoretical results, such as the uniformly subexponential tail probability (e.g., Li et al., 2012b), specific requirement for the mean response (e.g., Ma et al., 2017), or boundness of density functions of Y and X(k)$X_{(k)}$ (e.g., Wu & Yin, 2015; Xia & Li, 2021), the proposed method requires fewer conditions to derive the theoretical result. Finally, compared with Chatterjee (2021) who showed that trueω̂k$\widehat{\omega }_k$ converges almost surely to ωk$\omega _k$ as n$n \rightarrow \infty$, our result (11) gives the nonasymptotic result.…”
Section: Methodology and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, (11) indicates that the proposed method is able to handle the nonpolynomial (NP) dimensionality with p=ofalse{exp(n12κ)false}$p = o\lbrace \exp (n^{1-2\kappa })\rbrace$, which is parallel with other feature screening methods, such as distance correlation (Li et al., 2012b) or the rank concordance–based estimating equation (Ma et al., 2017). On the other hand, different from other feature screening methods that may require additional assumptions to establish theoretical results, such as the uniformly subexponential tail probability (e.g., Li et al., 2012b), specific requirement for the mean response (e.g., Ma et al., 2017), or boundness of density functions of Y and X(k)$X_{(k)}$ (e.g., Wu & Yin, 2015; Xia & Li, 2021), the proposed method requires fewer conditions to derive the theoretical result. Finally, compared with Chatterjee (2021) who showed that trueω̂k$\widehat{\omega }_k$ converges almost surely to ωk$\omega _k$ as n$n \rightarrow \infty$, our result (11) gives the nonasymptotic result.…”
Section: Methodology and Main Resultsmentioning
confidence: 99%
“…Moreover, as emphasized in Section 3.1, ω𝑘 is able to measure the correlation for the continuous or binary response with the predictor 𝑋 (𝑘) , it implies that ( 10) is valid to retain important predictors for models (1) and ( 2). This is one of main differences from other existing methods (e.g., Fan & Lv, 2008;Li et al, 2012b;Xia & Li, 2021). In addition, unlike Ma et al (2017), the measure (9) in the XI-SIS method is a model-free approach and is able to handle ties in responses and predictors.…”
Section: 2mentioning
confidence: 95%
See 1 more Smart Citation